4 mm cannulatedcancellous screws fixation in extra articular distal 1/3 radius fracture - A study - M.S. Patil; M.W. Khan; Faisal A. Mallick (Al Ameen Medical College, 2017)
Background: Distal radius fracture are extremely common and represents 16% of fractures treated by orthopaedic surgeons. Near anatomical reduction with restoration of radial length, radial tilt and ulnar variances are important for good functional results. Cannulated 4 mm long threaded using minimally invasive osteosynthesis technique are less aggressive towards soft tissue covering. It allows immediate range of motion of the wrist while maintaining alignment resulting in rapid and comfortable functional recovery. The objective of this study was to evaluate the clinical, radiological and functional efficacy of 4 mm cannulated screws in the management of extra articular distal radius fracture using the criteria of Gartland and Werley point system. Material & Method: 40 Patients with extra articular distal radius fracture were treated by minimally invasive osteosynthesis technique using 4 mm cannulatedcancellous screws in AL-Ameen Medical College Hospital, Bijapur between Nov 2013 to Oct 2015 which included 19 males and 21 female patients. The duration of follow-up was ranged from 12-18 months. Results: Using Demerit scoring system of Gartland and Werley, we had 45% excellent, 50% good, 0% fair and 5% poor results. As per our results, excellent to good results were found in 95% of patients. Conclusion: Cannulatedcancellous screws fixation is an effective means of fixation in distal 1/3 radius fracture, allowing immediate range of motion of the wrist, resulting in a rapid and comfortable functional recovery while maintaining alignment and bone healing. It has higher degree of purchase when treating extra articular distal radius fracture with poor bone quality. Being minimally invasive with minimal soft tissue dissection, less operative time, cost effective, cannulated screws is a good option for both young and elderly patients with extra articular distal radius fracture.